Ibn al-Arabi and his exegetical sources in his book “The Rulings of the Qur’an” - Kambal, Awad Mohammed Ahmed (Journal of Islamic Sciences, 2021)
The study of the study of this subject to the study of the psychology of the study in the study conducted in the study, and the method that it deals with in interpreting the source itself, which is to talk about its explanatory sources in his aforementioned book. On the curriculum those sources scattered in that book, and the researcher divided the study into an introduction, a chapter and a conclusion, and the most prominent and important results were as follows:That Ibn al-Arabi was influenced by those who preceded him among the commentators is clear in a way, And that these many narrations indicate his knowledge, navigation and high heels, including that he does not transmit from these exegetes in any case a Muslim quotation. Ibn Jarir al-Tabari, and with the status of Ibn Jarir al-Tabari, you see him responding to him in some cases with a strong and stinging phrase, and one of the important results is also - Ibn al-Arabi quoted from his many books on interpretation and others, in the interpretation it is noted that he refers to his book (Anwar al-Fajr), and his book (The Law of Interpretation) in interpretation). These were the most prominent and important results.
Keywords: And his exegetical sources; in his country in Seville; Muslim quotation; the beasts were shot; the mukhairat; some of my sheikhs; he wrote it with his finger